El papel de la computadora en la escuela: contraste entre teoría y práctica en docentes costarricenses de primaria y secundaria - Monge Nájera, Julián (2012)
In Costa Rica, computer science is not a “new technology”; it is part of the daily life of teachers and students. Nevertheless, the value and adequate use of computers at school is still being debated among theoreticians. The debate has theoretical and practical sides. The theoretical side: should we teach how the computer is programmed or should we simply teach how to use it? The practical side: should the computer be used in the classroom or only as an extra-classroom complement? We asked 231 female and male teachers from all Costa Rican regions and found that most of them favor teaching software use (not how the computer is programmed), both inside and outside the classroom. However, in real life, they mostly use the computer for administrative chores; they do not take advantage of the computer’s full potential for education. The expected results are still lacking. Costa Rican primary and secondary schools urgently need a radical turn in how teachers are trained and supported and in how computers are used.